Interaction of MutS and Vsr: Some Dominant-Negative mutS Mutations That Disable Methyladenine-Directed Mismatch Repair Are Active in Very-Short-Patch Repair - Lieb, Margaret (American Society for Microbiology, 2001)
In Escherichia coli and related bacteria, the very-short-patch (VSP) repair pathway uses an endonuclease, Vsr, to correct T · G mismatches that result from the deamination of 5-methylcytosines in DNA to C · G. The products of mutS and mutL, which are required for adenine methylation-directed mismatch repair (MMR), enhance VSP repair. Multicopy plasmids carrying mutS alleles that are dominant negative for MMR were tested for their effects on VSP repair. Some mutS mutations (class I) did not lower VSP repair in a mutS(+) background, and most class I mutations increased VSP repair in mutS cells more than plasmids containing mutS(+). Other plasmid-borne mutS mutations (class II) and mutS(+) decreased VSP repair in the mutS(+) background. Thus, MutS protein lacking functions required for MMR can still participate in VSP repair, and our results are consistent with a model in which MutS binds transiently to the mispair and then translocates away from the mispair to create a specialized structure that enhances the binding of Vsr.